2016
DOI: 10.6018/turismo.38.271401
|View full text |Cite
|
Sign up to set email alerts
|

Análisis longitudinal de los sitios web de las estaciones de esquí y montaña de España, Andorra y Pirineo de Francia. Temporadas 2009-10 y 2013-14

Abstract: <p>En el presente estudio se realiza un análisis longitudinal, entre las temporadas 2009-10 y<br />2013-14, de los sitios Web de las Estaciones de Esquí y Montaña de España, Andorra y Pirineo<br />de Francia, adaptando el modelo eMICA (Extended Model of Internet Commerce Adoption)<br />planteado por los autores Burgess y Cooper (2000) y adaptado por García y Escalera (2008).<br />Un método de carácter exploratorio, que recoge las características y funcionalidades que el<br />… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
5
0
4
Order By: Relevance
“…Published writings were thoroughly reviewed [51,[54][55][56][57][58][59][60], and a model constructed for a Web Content Analysis that was applied to ski resorts ( Table 1). The aim of this model is to provide an overview of the resources that ski resorts offer on their websites that enable users to obtain the necessary information and interact with the websites.…”
Section: Web Content Analysismentioning
confidence: 99%
“…Published writings were thoroughly reviewed [51,[54][55][56][57][58][59][60], and a model constructed for a Web Content Analysis that was applied to ski resorts ( Table 1). The aim of this model is to provide an overview of the resources that ski resorts offer on their websites that enable users to obtain the necessary information and interact with the websites.…”
Section: Web Content Analysismentioning
confidence: 99%
“…Other investigations detected weak exploitation of this instrument, revealing the need to reinforce resources and not to overlook the opportunities provided by the ICTs [6]. It has been confirmed that almost all ski resorts have their own websites, but a mere presence in the world of the Internet is not a factor that is, in itself, sufficient.…”
Section: Skiing Stations and Use Of Social Networkmentioning
confidence: 97%
“…Winter sports tourism takes place in a natural environment that, because of its characteristics, requires high levels of investment in infrastructure and maintenance [6]. Resorts should also have a strategy that considers sustainable forms of development that are both competitive and profitable [31].…”
Section: Skiing Sports Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different models to measure the maturity of websites, the E-MICA model has been widely used [19,[39][40][41]. E-MICA is a sequential model that is applied in different stages [42].…”
Section: E-mica Modelmentioning
confidence: 99%